Cryopolymerization‐enabled self‐wrinkled polyaniline‐based hydrogels for highly stretchable all‐in‐one supercapacitors. Issue 4 (4th July 2022) - Song, Hui; Wang, Yufeng; Fei, Qingyang; Nguyen, Dai Hai; Zhang, Chao; Liu, Tianxi
Abstract: Conductive polymer hydrogels are attractive due to their combination of high theoretical capacitance, intrinsic electrical conductivity, fast ion transport, and high flexibility for supercapacitor electrodes. However, it is challenging to integrate conductive polymer hydrogels into an all‐in‐one supercapacitor (A‐SC) simultaneously with large stretchability and superior energy density. Here, a self‐wrinkled polyaniline (PANI)‐based composite hydrogel (SPCH) with an electrolytic hydrogel and a PANI composite hydrogel as the core and sheath, respectively, was prepared through a stretching/cryopolymerization/releasing strategy. The self‐wrinkled PANI‐based hydrogel exhibited large stretchability (∼970%) and high fatigue resistance (∼100% retention of tensile strength after 1200 cycles at a 200% strain) ascribing to the formation of the self‐wrinkled surfaces and the intrinsic stretchability of hydrogels. Upon cutting off the edge connections, the SPCH could directly work as an intrinsically stretchable A‐SC maintaining high energy density (70 µW h cm −2 ) and stable electrochemical outputs under a stretchability of 500% strain and a full‐scale bending of 180°. After 1000 cycles of 100% strain stretching and releasing processes, the A‐SC device could deliver highly stable outputs with high capacitance retention of 92%. This study might provide a straightforward method for fabricating self‐wrinkled conductive polymer‐based hydrogels for A‐SCs with highly deformation‐tolerant energy storage. Abstract : It is challenging to develop new preparation methods of conductive polymer‐based composite hydrogels for constructing all‐in‐one supercapacitors (A‐SCs) with excellent deformation‐tolerant performance. Self‐wrinkled polyaniline‐based composite hydrogels (SPCHs) with large stretchability and excellent fatigue resistance are fabricated by a stretching/cryopolymerization/releasing strategy. The as‐obtained SPCH can work as an intrinsically stretchable A‐SC maintaining high energy density and stable electrochemical properties under deformations.